Psycho-philosophical structure of the concept of tazkiyatun nafs on the development of spiritual-emotional intelligence in students - Syafii, Hisyam; Alaldaya, Rudyn; Purnomo, Halim; Azhari, Husain (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
This research looks at the psycho-philosophical framework of the Tazkiyatun Nafs idea and how it affects college students' growth in spiritual-emotional intelligence. The study intends to: (1) investigate Tazkiyatun Nafs' ontological structure in the context of contemporary educational psychology; (2) investigate the epistemological aspects of Tazkiyatun Nafs in the development of spiritual-emotional intelligence; and (3) develop a conceptual model of the integration of Tazkiyatun Nafs within the framework of developing spiritual-emotional intelligence through a qualitative approach with a descriptive-analytical literature study method. The study's findings show that, in contrast to the traditional educational psychology method, which tends to isolate the cognitive, emotive, and spiritual elements of college students' growth, the ontological framework of Tazkiyatun Nafs provides an integrated picture of these aspects. The epistemological aspects of Tazkiyatun Nafs, according to this study, also include the process of knowledge acquisition that entails awareness change and the growth of the soul's perceptual powers, which combine experiential, intuitive, and intellectual knowledge. Four primary pedagogical techniques were found in this study's axiological aspect for use in higher education curricula: guided contemplative practice, transformational dialogic learning, interdisciplinary knowledge integration, and value-based critical reflection. These results offer a theoretical foundation for the creation of a more integrative and comprehensive educational paradigm that may accommodate students' multifaceted requirements in the contemporary period.